Feasibility of a new intervention addressing group-based balance and high-intensity training, physical activity, and employment in individuals with multiple sclerosis: a pilot randomized controlled trial - Arntzen, Ellen Christin; Braaten, Tonje; Fikke, Hanne Kristin; Normann, Britt (Frontiers in Rehabilitation Sciences, 2024)
Background and purpose: Impaired sensory-motor function, reduced physical activity and unemployment are common challenges in people with multiple sclerosis (pwMS), even when disability is low. CoreDISTparticipation is a new, multidisciplinary intervention systematically addressing these elements. The primarily aim was to evaluate the feasibility of CoreDISTparticipation in terms of process, resources, management and scientific outcomes. Secondary aim was to evaluate initial efficacy in terms of possible short-term effects compared to usual care on barriers to employment, balance, walking, healthrelated quality of life (HRQoL) and physical activity. Methods: This assessor-blinded prospective pilot randomized controlled trial included 29 pwMS (EDSS 0-3.5) randomly allocated to the CoreDISTparticipation intervention (n=15) or usual care (n=14). CoreDISTparticipation consists of: 1) hospital outpatient clinic; MS nurse work-focused session and physiotherapist exploring balance; 2) municipality; a digital meeting with pwMS, employer, MS nurse and physiotherapist addressing employment and physical activity, four weeks indoor CoreDIST balance training and four weeks outdoor CoreDIST balancetraining and high-intensity running/walking (60 minutes x2/week). Assessments at baseline, weeks 6 and 11. Primary feasibility metric outcomes were the reporting of process, resources, management and scientific outcomes. Efficacy measures included the Multiple Sclerosis Work Difficulties Questionnaire-23 Norwegian Version (MSWDQ-23NV) and Six Minute Walk-test, Trunk Impairment Scale-modified Norwegian Version, Mini-Balance Evaluation Systems Test, Multiple Sclerosis Walking Scale-12, Multiple Sclerosis Impact Scale-29, ActiGraph wGT3x-BT and AccuGait Optimized force platform. Statistical analyses included repeatedmeasures mixed models in IBM SPSS Version 29. Results: The primary feasibility metric outcomes demonstrated a need for minor adjustments in regard to content of CoreDISTparticipation and increasing number of staff. One person was excluded due to not attending post-intervention assessments, leaving 28 participants (mean EDSS 1.8, SD 1). The efficacy measures showed no between-group differences. Registeration in ClinicalTrials.gov (Identifier: NCT05057338).Discussion: CoreDISTparticipation is feasible to support pwMS when the identified feasibility metric outcomes regarding process, resource, management and scientific outcome metrics are adjusted to improve feasibility. No between-group differences were detected. A larger comparative trial can be conducted to explore between-group differences and should accurately and precisely define usual care and address the identified limitations..